2015
DOI: 10.1124/dmd.115.067561
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Cloning, Tissue Distribution, and Functional Characterization of Marmoset Cytochrome P450 1A1, 1A2, and 1B1

Abstract: The common marmoset (Callithrix jacchus), a New World monkey, has potential to be an animal model for drug metabolism studies. In this study, we identified and characterized cytochrome P450 (P450) 1A1 and 1B1 in addition to the known P450 1A2 in marmosets. Marmoset P450 1A1 and 1B1 cDNA contained open reading frames encoding 512 and 543 amino acids, respectively, with high sequence identities (90%-93%) to other primate P450 1A1s and 1B1s. A phylogenetic tree based on amino acid sequences showed close evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…CYP protein levels varied by 2–10 folds among microsomal samples from individual monkeys 33 , 34 . Several studies also characterized intestinal CYP expression in the common marmosets, another species of non-human primate 35 , 36 , 37 .…”
Section: Expression Of Drug-metabolizing Cyps In the Intestinementioning
confidence: 99%
“…CYP protein levels varied by 2–10 folds among microsomal samples from individual monkeys 33 , 34 . Several studies also characterized intestinal CYP expression in the common marmosets, another species of non-human primate 35 , 36 , 37 .…”
Section: Expression Of Drug-metabolizing Cyps In the Intestinementioning
confidence: 99%
“…To prepare the recombinant proteins, expression plasmids of marmoset and human P450 4F forms were constructed using pCW vectors containing a cDNA of human NADPH-P450 reductase as described previously (Uehara et al, 2016c). The N-terminal modification was performed by PCR using the forward and reverse primers containing the restriction sites of the NdeI and XbaI restriction enzymes (underlined), respectively, including cjCYP4F2 (5exp1bov) 59-CATATGG-CTCTGTTATTAGCAGTTTTTCTGGGCCTCGGGCCG-39 and cjCYP4F2 (3exp2) 59-TCTAGATTAGCTCAGGGGCTCCA-39 for marmoset P450 4F2, cjCYP4F2 (5exp1bov) 59-CATATGGCTCTGTTATTAGCAGTTTTTCTG-GGCCTCGGGCCG-39 and cjCYP4F3B (3exp2) 59-TCTAGATTAGCT-CCGGGGCTCCA-39 for marmoset P450 4F3B, cjCYP4F11 (5exp2bov) 59-CATATGGCTCTGTTATTAGCAGTTTTTCTGGGCCTCGGGCCAGTG-39 and cjCYP4F11 (3exp2) 59-TCTAGATTACTGTGGGTTTGCACCC-39 for marmoset P450 4F11, cjCYP4F12 (5exp1bov) 59-CATATGGCTCTGTTATT-AGCAGTTTTTCTGGGCTTCGGGCCAG-39 and cjCYP4F12 (3exp2) 59-TCTAGATTACTGTGAGCCCGCGT-39 for marmoset P450 4F12, hCYP4F2 (5exp1bov) 59-CATATGGCTCTGTTATTAGCAGTTTTTCTGGGCCTCTG-GCCAGTG-39 and hCYP4F2 (3exp1) 59-TCTAGATTAGCTCAGGGGCTC-CACCCGC-39 for human P450 4F2, hCYP4F3B (5exp1bov) 59-CATA-TGGCTCTGTTATTAGCAGTTTTTCTGGGCCTTTGGCCAATG-39 and hCYP4F2 (3exp1) 59-TCTAGATTAGCTCAGGGGCTCCACCCGC-39 for human P450 4F3B, cjCYP4F11 (5exp2bov) 59-CATATGGCTCTGTTAT-TAGCAGTTTTTCTGGGCCTCGGGCCAGTG-39 and hCYP4F11 (3exp1) 59-TCTAGATTACTGTGAGTTCGCACCCAGG-39 for human P450 4F11, hCYP4F12 (5exp1bov) 59-CATATGGCTCTGTTATTAGCAGTTTTTCT-GGGCCTCAGACCGGTG-39 and hCYP4F12 (3exp1) 59-TCTAGAT-TACTGCAAGCTTACATTCAGG-39 for human P450 4F12, and Human 4F2 93 91 84 81 4F3B 90 93 82 81 4F11 86 86 89 82 4F12 82 82 81 87 Cynomolgus monkey 4F2 91 90 84 82 4F3B 90 91 83 81 4F11 83 85 85 79 4F12 81 81 80 88 Marmoset 4F2 91 84 81 4F3B 83 81 4F11 80 Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicated that P450 2E1 enzymes had similar substrate specificities and catalytic activities among humans, cynomolgus monkeys, and marmosets. Our separated studies collectively indicated that other drug‐metabolizing forms of marmoset P450 enzymes effectively metabolized typical human P450 probe substrates: oxidations of ethoxyresorufin, ethoxycoumarin, and phenacetin by marmoset P450 1A2; S ‐warfarin, flurbiprofen, and omeprazole by marmoset P450 2C19; metoprolol, bufuralol, and dextromethorphan by marmoset P450 2D6; and midazolam, nifedipine, and testosterone by marmoset P450 3A4 (Uehara, Uno, Inoue, Sasaki, & Yamazaki, ; Uehara, Uno, Inoue, et al, ; Uehara, Uno, Hagihira, et al, ; Uehara et al, ). Taken together, marmosets may be good animal models for evaluating P450‐dependent drug oxidation in preclinical testing.…”
Section: Resultsmentioning
confidence: 74%